Study of changes in non-stress test following antenatal corticosteroid therapy in preterm pregnancy - S., Renuka; S., Sathiya; M., Famida A.; K., Vijayalakshmi; R., Sailatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preterm birth is the largest unsolved problem in obstetrics and the single most significant cause of neonatal morbidity and mortality. Preterm labour constitutes 5-10% of pregnancies and is the leading cause of neonatal morbidity and mortality worldwide. It is a major public health problem in terms of loss of life, long term disability (cerebral palsy, blindness, deafness, chronic lung disease). The objectives of this study were to determine whether antenatal corticosteroid administration affects the non-stress test. To evaluate the effect of antenatal steroid on foetal movements. To assess the incidence of respiratory distress syndrome and neonatal mortality after antenatal corticosteroid administration. Methods: All antenatal cases between 28-32 weeks of gestation judged to be at risk for preterm delivery attending the outpatient department or admitted in a tertiary care hospital, Tamil Nadu during the study period of 3 years. Results: The present study was undertaken to evaluate the NST for a period of 3 days following antenatal corticosteroid administration and to study the immediate changes in the mother and the foetus. We found out that there was a statistically significant change (p <0.01) in non-stress test when compared with the pre-betamethasone assay. Conclusions: Corticosteroids can cause metabolic alterations in mother, short- and long-term effect in the foetus.